PENGARUH RISIKO, RETURN DAN RELIGIUSITAS TERHADAP KEPUTUSAN INVESTASI MAHASISWA (Studi Pada Mahasiswa FEBI UIN STS Jambi) - Ahmad Syahrizal; Ahmad Syukron Prasaja; Lia Anjeli (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study aims to determine the effect of risk, return and religiosity on investment decisions in FEBI UIN STS Jambi students. The methods used in this study are quantitative methods, and the data analysis methods used are multiple regression, t test and f test. The sample in this study was 94 samples of students of FEBI UIN STS Jambi batch 2017-2020, by distributing Likert scale questionnaires. The test results obtained from the t test show that the risk variable (X 1) does not have a significant effect on Student Investment (Y). this is evidenced from the value of T calculated > Ttable , which is -1.439 < 1.66 and a significant value of 0.154 > 0.005 so that it can be concluded that H a dit olak and Ho diterima, while the variable return (X2) has a significant effect on student investment (Y). this is evidenced from the calculated T value > Ttable, which is 4.400 > 1.66 and a significant value of 0.002 < 0.005 so that it can be concluded that H a is accepted and Ho is rejected, then the variable of religiosity (X3) significant effect on student investment (Y). this is evidenced from the value of T calculated > Ttable which is 3.172 > 166 and a significant value of 0.00 2 < 0.005 so that it can be concluded that H a is accepted and H0 is rejected. The test results obtained from the f test show that the variables risk, return and religiosity simultaneously have a significant effect on student investment. This is evidenced from the value of F calculated> Ftable, which is 8,558 > 2.47 and a significant value of 0.001< 0.005 so that it can be concluded that H a is accepted and H0 is rejected. The influence on the independent variables (X 1), (X 2) and (X3) was 19.8% while the remaining 80.2% was influenced by other variables outside this study